Does Islamic Microfinance Affect the Reduction of Poverty Post the Covid-19 in Parepare? - Nun Maziyyah Mahsyar; St Nurhayati Ali; Mahsyar Idris (Jurnal Ilmiah Ekonomi Islam, 2023)
The coronavirus has spread worldwide since the end of two thousand nineteen. The coronavirus outbreak affects many elements of life, particularly the household economy. The number of job losses led to a significant number of persons living in poverty. One approach to relieving poverty is to offer financial assistance to the beneficiaries. Baitul Mal Wat Tamwil Fauzan Azhiima is an Islamic microfinance institution in Parepare providing financial assistance to middle-low income. The authors will focus on Parepare because it is one of the small cities in South Sulawesi which becomes the center of covid-19 aid. This study aims to analyze the relationship between BMT and poverty reduction post-coronaviruses in Parepare. This study uses a qualitative approach, particularly conducting interviews with beneficiaries post-financing. As a result, the financing of BMT which is Murabahah, Qard Al-Hasan, and Mudarabah contracts affect the improvement of life, supports education, boosts the income level, and in the end breaks the poverty line in Parepare.